Cowboy charming - Crush, Dylann (Crush, Dylann. Holiday, Texas, 2019)
"Small-town preacher's daughter Dixie King is used to having a lot on her plate. Keep tabs on her flighty grandmother? No problem. Handle the honky-tonk's first ever Chili Cook-Off? In the bag. Vamp it up to charm a would-be developer into leaving Holiday, Texas for good? ...Now there she might need a helping hand. Enter Presley Walker: Holiday's own Cowboy Casanova and the perfect tutor for a good girl looking to go bad. He's got charm in spades, and he's always seemed like a terrible idea waiting to happen. But as Presley and Dixie work together to save their beloved hometown, these polar opposites might finally see the good in each other...if they can only learn to trust their hearts enough to fall.""--Provided by publisher.